1999
DOI: 10.1007/pl00011746
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Transgenic Tilapia with Accelerated Growth

Abstract: Recent advances in modern marine biotechnology have permitted the generation of new strains of economically important fish species through the transfer of growth hormone genes. These transgenic fish strains show improved growth performance and therefore constitute a better alternative for aquaculture programs. Recently, we have obtained a transgenic tilapia line with accelerated growth. However, before introducing this line into Cuban aquaculture, environmental and food safety assessment was required by nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
(35 reference statements)
1
22
0
4
Order By: Relevance
“…for tilapia) or from another fish species. The evaluation of the safety of consuming tiGHtransgenic tilapia included a study of the effects of injection of recombinant tiGH into macaques, and a test of the in-vitro activity of tiGH on rabbit xiphoid cartilage bioassay [84]. From the results from both experiments the conclusion was drawn that tiGH had no effect on the metabolism of higher vertebrates and, especially, no biological activity in nonhuman primates.…”
Section: The Gene Productmentioning
confidence: 78%
“…for tilapia) or from another fish species. The evaluation of the safety of consuming tiGHtransgenic tilapia included a study of the effects of injection of recombinant tiGH into macaques, and a test of the in-vitro activity of tiGH on rabbit xiphoid cartilage bioassay [84]. From the results from both experiments the conclusion was drawn that tiGH had no effect on the metabolism of higher vertebrates and, especially, no biological activity in nonhuman primates.…”
Section: The Gene Productmentioning
confidence: 78%
“…for tilapia) or from another fish species. In the case of the transgenic GH fish, specific experimental evidence that teleost GH is not active in primates was obtained by Guillen et al [30]. Juvenile monkeys, Macaque fascicularis (macques) were injected with 1000 ng/kg of recombinant tilapia growth hormone per day for 30 days, equivalent to administering 70 g/day to a 70 kg human.…”
Section: The Gene Productmentioning
confidence: 99%
“…Juvenile monkeys, Macaque fascicularis (macques) were injected with 1000 ng/kg of recombinant tilapia growth hormone per day for 30 days, equivalent to administering 70 g/day to a 70 kg human. Guillen et al [30] have shown that blood parameters examined included hemoglobin, serum total proteins, blood glucose, packed cell column, total leukocytes, and total erythrocytes. Body weight, rectal temperature, heart rate, and respiratory rate were recorded daily.…”
Section: The Gene Productmentioning
confidence: 99%
See 2 more Smart Citations